2017
DOI: 10.1186/s12955-017-0796-4
|View full text |Cite
|
Sign up to set email alerts
|

The development and psychometric properties of the Arabic version of the child oral health impact profile-short form (COHIP- SF 19)

Abstract: BackgroundThis study aims to cross-culturally adapt the original English-language COHIP-SF 19 to Arabic culture and to test its psychometric properties in a community sample.MethodsThe Arabic COHIP-SF 19 was developed and its psychometric properties were examined in a population-based sample of 876 schoolchildren who were aged 12 years of age, in Benghazi, Libya. The Arabic COHIP-SF 19 was tested for its internal consistency, reproducibility, construct validity, factorial validity and floor as well as ceiling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 38 publications
7
21
2
Order By: Relevance
“…The construct and discriminant validity tests revealed that the Indonesian version of the SEOH was significantly correlated with the adolescents’ satisfaction with oral health. There were no floor or ceiling effects of the developed questionnaire in this study because none of the respondents achieved the lowest or highest possible score . Although there was no difference in terms of the mean total score of the SEOH questionnaire between males and females, there was a significant difference in terms of the self‐efficacy for psychological control.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The construct and discriminant validity tests revealed that the Indonesian version of the SEOH was significantly correlated with the adolescents’ satisfaction with oral health. There were no floor or ceiling effects of the developed questionnaire in this study because none of the respondents achieved the lowest or highest possible score . Although there was no difference in terms of the mean total score of the SEOH questionnaire between males and females, there was a significant difference in terms of the self‐efficacy for psychological control.…”
Section: Discussionmentioning
confidence: 65%
“…There were no floor or ceiling effects of the developed questionnaire in this study because none of the respondents achieved the lowest or highest possible score. 33 Although there was no difference in terms of the mean total score of the SEOH questionnaire between males and females, there was a significant difference in terms of the self-efficacy for psychological control. This result differs from that of a previous study which reported that female adults had a higher total SEOH questionnaire score and greater self-efficacy in daily life habits.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Parental perception of the OHRQoLwas recorded using the validated Arabic version of the child oral health impact profile-short form . 16 In addition to the questionnaire, a general question regarding the parents' overall experience with nasoalveolar molding was added for the group with cleft lip and palate.…”
Section: Recording Of Ohrqolmentioning
confidence: 99%
“…The child oral health impact scale-short form (COHIP-SF) is a validated measure that seeks to determine the perception of a child's OHRQoL through 19 questions in three major domains. 16 The questionnaire has been recently validated in Arabic. 16 This study aimed to assess the OHRQoL of children aged below 5 years of age who had cleft lip and palate who were undergoing nasoalveolar molding prior to surgery and compare these to ageand gender-matched controls using the validated Arabic version of the COHIP-SF.…”
Section: Introductionmentioning
confidence: 99%